The effect of variations in vulcan concentration in agel-cotton rope as a reinforcement for ripoxy composites on thermal conductivity properties - I.K. Suarsana; I.G.N.N. Santhiarsa; I.G.N.P. Tenaya; A.R.F. Tarigan; A.A.A. Triadi (Universitas Mataram, 2025)
Ripoxy composites reinforced with natural agel-cotton rope reinforcement have attracted attention in engineering material applications due to their mechanical properties and environmentally friendly waste. Vulcan chemicals, which are fillers or additives in the composite manufacturing industry, are believed to be able to improve the thermal properties of the composite. This study aims to examine the effect of vulcan chemical treatment on thermal conductivity in ripoxy composites reinforced with cotton rope. This test was carried out by soaking agel-cotton rope textiles in Vulcan solution for 1 hour with variations in solution concentration: 0%, 25%, and 50%. The printing of test specimens was carried out using a Vacuum Infusion printing tool, so that the printed specimen results were not contaminated by outside air. Thermal conductivity tests were carried out using the ASTM - D5470 standard. The test results that have been obtained, the 25% concentration variation has the smallest thermal conductivity value, with a value of 0.064 W / m°C at a temperature of 100° C and 0.171 W / m°C at a temperature of 200°C. Meanwhile, with a concentration variation of 50% the value increases because the greater the concentration of Vulcan given, the density of the composite material will increase, and higher concentrations can reduce the number of pores or voids in the composite which can usually inhibit heat flow.